Quality of Immediate Nursing Care Provided to Newborn at Maternity Teaching Hospital in Erbil City - Kurdistan Mirza Jamsheer; Norhan Zeki Shaker (Hawler Medical University, 2018)
Background and objective: Quality of nursing care and competent health care providers, particularly skilled birth attendants, are essential requirements for providing care for both mothers and newborns. The current study aimed to assess quality of nursing care provided immediately after birth to newborn by nurse/midwives at Maternity Teaching Hospital in Erbil city. Methods: An observational study conducted during 2014. Samples of 25 nurse/midwives were purposively selected from nurses working at delivery room. Data were collected through the use of questionnaire format and observation checklist structured by researcher. The questionnaire format was used for interviewing nurse/midwives about (socio-demographic, professional background and nurses/midwives workload), while the check-list, which consisted of eight domains, was used for observing nurse/midwives during new-born care. A panel of experts checked the validity of the instrument when reliability was measured with computation of Pearson product moment correlation. Data were analyzed through the application of descriptive and inferential statistical tests. Results: The results revealed that the highest percentage 40% of the nurse/midwives were graduated from preparatory midwifery school, 64% of the nurse/midwives haven't attended training course about immediate neonatal care. 100% of nurse /midwives do not washed their hands before and after performing each procedure and haven't any role in initiation of newborns breathing. There were not significant associations between overall quality of immediate nursing care and nurse/midwife's qualification, experience years and training course. Conclusion: Quality of immediate nursing care provided after birth to newborn by most of nurse/midwives was poor.